There are movies that hurt: sensations of pain in cinema from a cognitive perspective - Víctor Aertsen (Index Comunicación, 2017)
Few viewers can deny having contracted in pain at the face of an explicit image of a fracture, a cut or a ripping, or beening infected by the intense suffering that the expressions of some character denoted. In spite of this, little research has gone into the study of the aesthetic and psychophysical mechanisms of cinematographic pain. Based on the findings of the most recent research in the area of cognitive neurosciences, this paper surveys some of the ways in which an audiovisual device can provoke pain sensations in its viewers, taking into account the relationship between body factors and aesthetic strategies that modulate them. This casuistry is accompanied by a series of concrete examples that analyze the strategies followed for its elicitation, as well as the way in which these feelings are integrated into the complete experience of each scene.